The Effect of Caring Behavior in Overcoming Anxiety in Ischemic Heart Disease (IHD) Patients Undergoing Percutaneous Atrial Catheter (PAC) - Sri Endhang Rahmawati; Suksi Riani; Dwi Fitriyanti (UrbanGreen, 2023)
The prevalence of heart disease in Indonesia reaches 1.5% in the population of all ages, which means that among 100 people of all ages 1.5 suffer from heart disease. Central Java province ranks 8th with a prevalence of 1.6 of the total population. Ischemic Heart Disease (IHD) patients who are pro PAC procedures at the emergency room SMC RS Telogorejo experienced physical and psychological problems. This study aims to influence the caring behavior of nurses in overcoming anxiety in IHD patients undergoing percutaneous atrial catheter (PAC). This method research used a quasy experiment with one group pretest posttest design. The number of samples were 45 respondents with data collection techniques using total sampling. This research use Wilcoxon test. The results showed that there was an effect of nurse caring behavior in reducing anxiety patients undergoing PAC at the ER SMC Telogorejo (p value = 0.000). Therefore, nurses are expected to give caring behavior for reduce anxiety levels in IHD patients undergoing PAC.